2013
DOI: 10.1122/1.4763567
|View full text |Cite
|
Sign up to set email alerts
|

Increase of long-chain branching by thermo-oxidative treatment of LDPE: Chromatographic, spectroscopic, and rheological evidence

Abstract: SynopsisLow-density polyethylene was thermo-oxidatively degraded at 170 C, i.e., degraded in the presence of air, by a one thermal cycle (1C) treatment during times between 30 and 90 min, and by a two thermal cycles (2C) treatment, i.e., after storage at room temperature, an already previously degraded sample was further degraded during times between 15 and 45 min. Characterization methods include gel permeation chromatography (GPC), Fourier transform infrared (FTIR) spectroscopy, as well as linear and nonline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 71 publications
2
9
0
Order By: Relevance
“…5 Comparison of elongational viscosity data (symbols) of LDPE III to LDPE VI measured by RME rheometer (Bastian 2001), as well as LDPE 1840D (Rolón-Garrido et al 2013), Escorene and Bralen (Pivokonsky et al 2006) measured by SER rheometer and characterized in Tables 2, 3 and 4 with predictions of HMMSF model (continuous lines) using the RME rheometer, as well as LDPE 1840D (Rolón-Garrido et al 2013), Escorene and Bralen (Pivokonsky et al 2006) measured by the SER rheometer. The elongational viscosity data of LCB-PP (Wagner et al 2006) measured by the MTR are shown in Fig.…”
Section: Comparison Between the Predictions Of The Hmmsf Model And Thmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Comparison of elongational viscosity data (symbols) of LDPE III to LDPE VI measured by RME rheometer (Bastian 2001), as well as LDPE 1840D (Rolón-Garrido et al 2013), Escorene and Bralen (Pivokonsky et al 2006) measured by SER rheometer and characterized in Tables 2, 3 and 4 with predictions of HMMSF model (continuous lines) using the RME rheometer, as well as LDPE 1840D (Rolón-Garrido et al 2013), Escorene and Bralen (Pivokonsky et al 2006) measured by the SER rheometer. The elongational viscosity data of LCB-PP (Wagner et al 2006) measured by the MTR are shown in Fig.…”
Section: Comparison Between the Predictions Of The Hmmsf Model And Thmentioning
confidence: 99%
“…The comprehensive aspects of this commercial rheometer, as well as the rheological theories behind it, have been explained elsewhere (Meissner and Hostettler 1994;Narimissa et al 2015). Rolón-Garrido et al (2009, 2013 and Pivokonsky et al (2006) conducted their uniaxial elongational measurements of Lupolen 1840D, Escorene and Bralen through Sentmanat Extensional Rheometer (Sentmanat 2004) universal testing platform from Xpansion Instruments, i.e. models SER2-P and SER-HV-A01, respectively.…”
Section: Rheological Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental techniques applied were the solvent extraction method, rheology and Fourier transform infrared (FTIR) spectroscopy. In contrast to thermo- [9] and thermo-oxidative degradation [9,10], the linear viscoelastic response of the samples, measured in small amplitude oscillatory shear flow, was found to be strongly affected by the photooxidative degradation [7]. The rheological data obtained in the nonlinear regime, i.e.…”
Section: Introductionmentioning
confidence: 49%
“…In order to stabilize the polymer processing, it is very important to understand all possible structural changes of the particular polymer due to thermal degradation. It has been shown that rheology can be used as the powerful tool to understand degradation of different polymers due to its sensitivity to very small changes in the molecular structure of polymers as well as to understand their molecular structure via utilization of advanced constitutive equations, which are based on the molecular arguments [1][2][3][4][5][6][7][8][9][10]. With the aim to extend the knowledge in this area, thermal stability of branched polypropylene was investigated in this work by using basic rheological tool and methodologies.…”
Section: Introductionmentioning
confidence: 99%